Modulation of Adipocytokines Production and Serum NEFA Level by Metformin, Glimepiride, and Sitagliptin in HFD/STZ Diabetic Rats - Mohamed I. Saad; Maher A. Kamel; Mervat Y. Hanafi (Biochemistry Research International)
Type 2 diabetes mellitus (T2DM) is a group of metabolic disorders characterized by hyperglycemia owing to insulin resistance and/or insulin deficiency. Current theories of T2DM pathophysiology include a decline in β-cells function, a defect in insulin signaling pathways, and a dysregulation of secretory function of adipocytes. This study aimed to investigate the effect of different antidiabetic drugs on serum levels of certain adipocytokines and nonesterified fatty acids (NEFA) in high-fat diet (HFD)/streptozotocin- (STZ-) induced diabetic rats. All treatments significantly decreased serum NEFA level. Metformin and sitagliptin increased serum adiponectin level, whereas they decreased serum leptin level. Glimepiride showed significant decline in serum levels of both adiponectin and leptin. All treatments remarkably ameliorated insulin resistance, suggested by an improvement of glycemic control, a significant reduction in homeostasis model assessment of insulin resistance (HOMA-IR), and a correction in lipid profile. Modulation of adipocytokines production (i.e., increased serum adiponectin and decreased serum leptin) may also underlie the improvement of insulin resistance and could be a possible mechanism for the beneficial cardiovascular effects of metformin and sitagliptin.